Hiv-Associated Neurocognitive Disease: Case Studies and Suggestions for Diagnosis and Management in Different Patient Subgroups. Issue 1 (January 2014) - Pozniak, Anton; Rackstraw, Simon; Deayton, Jane; Barber, Tristan; Taylor, Steve; Manji, Hadi; Melvin, Diane; Croston, Michelle; Nightingale, Sam; Kulasegaram, Ranubabu; Pitkanen, Mervi; Winston, Alan
The incidence of HIV-associated dementia has decreased significantly with the introduction of combination antiretroviral therapy; however, milder or more subtle forms of neurocognitive disorders associated with HIV appear to remain common. There is a lack of consensus on when to screen and on which methods are most appropriate for identifying patients at risk of neurocognitive impairment. Multiple factors (demographic, social, genetic, psychological and medical) can play a role in its aetiology and progression, including potential central nervous system toxicity of antiviral therapy. It is important to identify these factors in order to apply relevant management strategies. In this review, we discuss a series of case studies that address some of the challenges presented by the diagnosis and management of HIV-associated neurocognitive impairment in different patient types.